The role of strategic thinking in achieving government innovation: A filed study on the employees of Ministry of Justice in Jeddah - Alzhrani, Seham Sharaf; Shuaibi, Faisal Ahmad (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aimed to know the role of strategic thinking in its four dimensions (holistic thinking, abstract thinking, diagnostic thinking, and schematic thinking) in achieving government innovation from the employee’s views at the Ministry of Justice in Jeddah Provence. In the response of the study sample towards the relationship between two variables (strategic thinking and government innovation), due to the following personal variables (gender, age, educational qualification, years of experience, job title, job rank, and job type). The study applied the descriptive analytical approach and adopted the questionnaire as a main tool for collecting study data from 640 employees. The main results of the study were: There was a role for the strategic thinking on achieving government innovation among employees at the Ministry of Justice in Jeddah Provence. The study found that there was a statistically significant relationship at the level (α ≤ 0.05) for the strategic thinking in its four dimensions (holistic thinking, abstract thinking, diagnostic thinking, and schematic thinking) and government innovation. The study also revealed that there was a statistically significant differences in the relationship between the two variables of the study (strategic thinking and government innovation) due to the variables of age and type of job. The results indicated that there was no a statistically significant differences in the relationship between the two variables (strategic thinking and government innovation) due to the following personal variables (gender, educational qualification, experience, job title, and job rank). The study recommends to seriously implement strategic thinking and its dimensions in public organizations, It needs to continue training employees to analyze various environmental factors, predict upcoming opportunities and challenges.